Comparative Analysis of Dorsal Distraction Plating Versus External Fixation in the Management of Intra-Articular Distal Radius Fractures - Ismail Pandor; Abhishek Sharma; Paresh Patil; Sushant Pandit; Prathamesh Karad; Alim Shaikh (Journal of Orthopaedic Case Reports)
Introduction: Fractures located in close proximity to the lower end of the radius bone, which make up around 16% of fractures requiring emergency treatment require careful treatment to regain mobility in the wrist joint and the fingers. Although classic external fixation (ExFix) methods are widely used, newer procedures such as dorsal distraction plating are showing potential . This study investigates the concepts, debates, and results of several methods so that to determine the most effective fracture treatment. Materials and Methods: The experiment will recruit individuals with intricate fractures affecting the joint across the distal region of the radius. The patients will be randomly randomized to receive either dorsal distraction plating or ExFix. Pre-operative, post-operative, and follow-up assessments will involve clinical and radiographic examinations. Functional outcomes will be evaluated using standardized scoring systems . A comparative statistical analysis will be performed to assess the outcomes obtained from both groups. Results: The average ages across the bridge plate and ExFix sections were 40 and 43 years, respectively. The cohort of patients who had bridge plating exhibited a greater prevalence of male individuals (P = 0.011). The ExFix group had elevated infection rates, which can be ascribed to the occurrence of pin tract infections. Both the groups did not show any instances of nerve palsy. Patients who received dorsal distraction plating expressed higher levels of satisfaction with their post-operative results, both in terms of functionality and appearance . Discussion: Patients treated with dorsal distraction reported fewer issues. Although a few difficulties were observed, the most of these patients expressed high levels of satisfaction with the results of their surgical procedures . The findings suggest that dorsal distraction may offer a more favorable balance between functional recovery and patient satisfaction, highlighting a potential advantage over ExFix. In the long run, however, the functional outcomes of both the techniques were found to be similar. Conclusion: Dorsal bridge plating is a viable substitute for ExFix in treating distal radius fractures. The use of dorsal bridge plating demonstrated greater performance in daily activities, despite the fact that the functional and radiological findings at 6 months were found to be almost indistinguishable in both groups .